Safety and efficacy of long‐term tolvaptan therapy for decompensated liver cirrhosis. Issue 3 (23rd July 2015) - Kogiso, Tomomi; Tokushige, Katsutoshi; Hashimoto, Etsuko; Ikarashi, Yuichi; Kodama, Kazuhisa; Taniai, Makiko; Torii, Nobuyuki; Shiratori, Keiko
Abstract : Aim: Recently, the short‐term efficacy of the vasopressin V2 receptor antagonist tolvaptan for the treatment of ascites in cirrhosis was reported. However, the long‐term effects remain unknown. Here, we report the clinical features of decompensated cirrhosis treated using long‐term tolvaptan therapy, and evaluate its safety and efficacy. Methods: Fifty‐five cirrhotic patients hospitalized due to ascites, despite receiving appropriate diuretic treatment, were treated with tolvaptan. We excluded 35 patients due to liver transplant (20.0%), death (28.6%), poor general status (14.3%), improved ascites (5.7%) or other reasons (31.4%). In 20 cases treated with tolvaptan for 6 months, total body water (TBW) and extracellular fluids (ECW) were measured using bioelectric impedance analysis (BIA) with an InBody720. Results: The median age of the 20 patients was 64 years (range, 48–90), and 60% were male. The etiology of cirrhosis included hepatitis C (45%), alcohol‐induced (20%) and other (35%). The percentage of patients with Child–Pugh class A, B and C was 0%, 40% and 60%, respectively. Biochemical findings revealed that serum creatinine levels and estimated glomerular filtration rate were not affected during 6 months of treatment with tolvaptan, and there was no renal disturbance. The median serum sodium levels were increased from 138 to 139 mEq/L, but serious adverse events related to renal and liver function were not observed. Data also revealed that long‐term treatment reduced the BIA‐estimated ECW/TBW ratio. Conclusion: Long‐term tolvaptan treatment was a safe and effective treatment for decompensated cirrhosis.